Reading R.S. Peters today : analysis, ethics, and the aims of education - Cuypers, Stefaan E., 1958-; Martin, Christopher; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2011)
"No one in the development of modern, analytical philosophy of education has played so dominant a role as British philosopher Richard Stanley Peters. Seeking to bring clarity, argumentative structure, and a new seriousness to the discipline in the early 1960s, Peters also inspired and facilitated the growth of publication in the field. His prodigious output encompassed foundational conceptual analysis of education and teaching, examination of justifications of educational aims and the curriculum, and enquiry into ethical development and moral education. Reading R.S. Peters Today: Analysis, Ethics and the Aims of Education reassesses Peters' educational writings by exposing them to the critical glare of the most recent developments in philosophy and practice. Peters' work is analysed from a wide range range of perspectives, which, taken together, will reveal the extent to which his body of work survives as a serious contribution to central questions in ethics and epistemology, politics, and moral psychology. Contributions also show the ongoing significance of R.S. Peter for the field of education today. Reading R.S. Peters Today represents a timely and important critical reassessment of one of the founding fathers of contemporary philosophy of education"--
Front Matter -- Introduction: Reading R.S. Peters on Education Today / Stefaan E Cuypers, Christopher Martin -- The Conceptual Analysis of Education and Teaching. Was Peters Nearly Right about Education? / Robin Barrow -- Learning Our Concepts / Megan J Laverty -- On Education and Initiation / Michael Luntley -- Ritual, Imitation and Education in R.S. Peters / Bryan R Warnick -- Transformation and Education: The Voice of the Learner in Peters' Concept of Teaching / Andrea English -- The Justification of Educational Aims and the Curriculum. R.S. Peters' Normative Conception of Education and Educational Aims / Michael S Katz -- On the Worthwhileness of Theoretical Activities / Michael Hand -- Why General Education? Peters, Hirst and History / John White -- The Good, the Worthwhile and the Obligatory: Practical Reason and Moral Universalism in R.S. Peters' Conception of Education / Christopher Martin -- Overcoming Social Pathologies in Education: On the Concept of Respect in R.S. Peters and Axel Honneth / Krassimir Stojanov -- Aspects of Ethical Development and Moral Education. Reason and Virtues: The Paradox of R.S. Peters on Moral Education / Graham Haydon -- Autonomy in R.S. Peters' Educational Theory / Stefaan E Cuypers -- Peters in Context. Richard Peters and Valuing Authenticity / M A B Degenhardt -- Vision and Elusiveness in Philosophy of Education: R.S. Peters on the Legacy of Michael Oakeshott / Kevin Williams -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Peters, R. S. -- 1919-2011.; Peters, Richard Stanley, -- 1919-2011.; Peters, R. S. -- 1919-2011.; Education -- Philosophy; EDUCATION -- Philosophy & Social Aspects; Education -- Philosophy; Electronic books